2012
DOI: 10.1007/s10344-012-0686-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and microsatellite markers evidence a different pattern of hybridization in red-legged partridge (Alectoris rufa) populations from NW Italy

Abstract: Abstract.Genetic introgression with exotic genomes represents a major conservation concern for the red-legged partridge (Alectoris rufa, Phasianidae). In particular, massive releases of chukar partridges (Alectoris chukar) and/or red-legged x chukar partridge hybrids for hunting purposes have cast serious doubts on the Italian present-day occurrence of wild A. rufa populations not affected by introgressive hybridization. This study investigates the genetic structure of red-legged partridges populations in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 74 publications
1
21
0
1
Order By: Relevance
“…Our discovery that the naturalized population of East Anglia is also unsuitable for the genetic management of native A. r. rufa has further reduced the range of options available to carry out concrete conservation action for the populations from the easternmost part of the species' range. Luckily, a study has recently suggested the existence of a genetically well-preserved and selfsustaining A. rufa population in the Italian Peninsula (Negri et al 2013). The phylogenetic placement of this resource (sensu Fraser and Bernatchez 2001) within the A. rufa puzzle needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our discovery that the naturalized population of East Anglia is also unsuitable for the genetic management of native A. r. rufa has further reduced the range of options available to carry out concrete conservation action for the populations from the easternmost part of the species' range. Luckily, a study has recently suggested the existence of a genetically well-preserved and selfsustaining A. rufa population in the Italian Peninsula (Negri et al 2013). The phylogenetic placement of this resource (sensu Fraser and Bernatchez 2001) within the A. rufa puzzle needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…In captivity the chukar is the most prolific Alectoris breeder, and when crossed with RLPs, the offspring are equally prolific. Such an intensive management has led to the virtual loss of the native genome of A. r. rufa, which includes the most heavily genetically polluted populations of the species (Dias 1992;Baratti et al 2004;Barbanera et al 2005Barbanera et al , 2009aBarbanera et al , 2011Barilani et al 2007;Tejedor et al 2007;Blanco-Aguiar et al 2008;Martínez-Fresno et al 2008;Casas et al 2012;Negri et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…This decline is mostly associated with anthropogenic causes, including the massive release of captive-bred chukar partridge Alectoris chukar , Gray 1830, resulting in the formation of hybrids [3, 4, 5]. Genetic pollution and hybridization magnified the damages already caused by the decline of natural populations due to habitat loss and overhunting, and likely resulted from an uncertain morphological distinction between these species.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular markers have been proved to represent an effective tool to support management of Alectoris populations [3, 4, 5, 7, 8]. As in most conservation-oriented genetic studies, both mitochondrial DNA (mtDNA) and nuclear DNA (nDNA) were used [3, 4, 5, 7], offering different and complementary information on the history of populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation